Getting it right on mistakes. (12th October 2019) - Oxtoby, Catherine
Abstract : Mistakes are an inevitable part of both life and veterinary practice. But Catherine Oxtoby says there are ways to reduce the risk both of an error occurring and of it impacting on your wellbeing.